A Case of Functional (Psychogenic) Monocular Hemianopia Analyzed by Measurement of Hemifield Visual Evoked Potentials - Tsuyoshi Yoneda; Ken Fukuda; Mayu Nishimura; Atsuki Fukushima (Case Reports in Ophthalmology, 2013)
Purpose: Functional monocular hemianopia is an extremely rare condition, for which measurement of hemifield visual evoked potentials (VEPs) has not been previously described. Methods: A 14-year-old boy with functional monocular hemianopia was followed up with Goldmann perimetry and measurement of hemifield and full-field VEPs. Results: The patient had a history of monocular temporal hemianopia of the right eye following headache, nausea and ague. There was no relative afferent pupillary defect, and a color perception test was normal. Goldmann perimetry revealed a vertical monocular temporal hemianopia of the right eye; the hemianopia on the right was also detected with a binocular visual field test. Computed tomography, magnetic resonance imaging (MRI) and MR angiography of the brain including the optic chiasm as well as orbital MRI revealed no abnormalities. On the basis of these results, we diagnosed the patient's condition as functional monocular hemianopia. Pattern VEPs according to the International Society for Clinical Electrophysiology of Vision (ISCEV) standard were within the normal range. The hemifield pattern VEPs for the right eye showed a symmetrical latency and amplitude for nasal and temporal hemifield stimulation. One month later, the visual field defect of the patient spontaneously disappeared. Conclusions: The latency and amplitude of hemifield VEPs for a patient with functional monocular hemianopia were normal. Measurement of hemifield VEPs may thus provide an objective tool for distinguishing functional hemianopia from hemifield loss caused by an organic lesion.